Influência da adubação orgânica e de doses de material húmico sobre a produção de alface americana e teores de carbono no solo - Marchi, Edilene Carvalho Santos (2006)
Two works were developed aiming to test organic fertilization, liming, and levels of soil conditioner composed by humic and fulvic acids on the growth and yield of the "iceberg" lettuce and soil organic carbon on Oxisol and Inceptsol. The first work evaluated the effect of organic fertilization, liming, and levels of soil conditioner composed by humic and fulvic acids on the "iceberg" lettuce growth and yield. The second work evaluated the influence of these treatments on the soil organic carbon and its fractions (humic, fulvic and the relation humic/fulvic). Two experiments were carried out at the Soil Science Department of the Federal University of Lavras, Minas Gerais State, Brazil, from March to July 2005, under a greenhouse. The experimental design was completely randomized in a 5x3x2 factorial scheme, in which 5 levels of soil conditioner (0, 20, 40, 100, 200 L ha-1), 3 types of fertilization (organic compost, chicken manure and mineral), and liming (with and without) using five replications were applied. The first work evaluated the total dried and fresh biomass, commercial dried and fresh biomass, plants height, lettuce head average diameter, average number of leaves, and dried root weight. The chicken manure rendered the best root growth and dried biomass. The soil conditioner composed of humic substances did not influence on plant growth, except on the height of plants cultivated on the Inceptisol. The liming was very important on mineral fertilization treatments for the yield of lettuce grown in the Oxisol. On the second work, soil samples were collected using three replicates. The soil organic carbon and its fractions (humic, fulvic and relations humic/fulvic) were evaluated. In the Inceptisol essay, the liming contributed to a decrease in the organic-C content in the mineral and compost fertilized plots, and increased the C accumulation in the treatments under chicken manure. The organic fertilizer increased the content of C-humic acid and the relation C-AH/AF. In the Oxisol essay, the use of liming contributed to the C accumulation when related to the treatments without use of liming. The effects of liming and the fertilizers varied in function of analyzed organic fractions and C content.